PREPARATION AND CHARACTERIZATION OF Mn (III) COMPLEXES (Journal of Sciences, Islamic Republic of Iran)
We have prepared and characterized a few Mn (III) complexes by using a few bidentate and tridentate ligands. Spectra of the manganese (III) ion in a variety of molecular environments are reported. On the basis of solution spectra, some of these complexes seem to be typically distorted